The Role of Employee Engagement in the Implementation of Total Quality Management at SD Negeri 001 Gunung Tabur - Eli Sutrisnaniati; Nurlelawati; Azainil (EduLine: Journal of Education and Learning Innovation, 2024)
Total Quality Management (TQM) is a comprehensive approach to improving the quality of education through the active participation of all members within the institution. This study examines the role of employee engagement in the implementation of TQM at SD Negeri 001 Gunung Tabur, along with its factors and challenges. The research employs a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. The results indicate that employee engagement, including teachers and administrative staff, plays a significant role in the application of TQM from planning, implementation, to evaluation. This engagement is reflected in various aspects, such as commitment to quality improvement, team collaboration, and active participation in teacher competency enhancement training. The challenges faced include human resource limitations, such as employees' lack of understanding of the importance of TQM, and material limitations, such as infrastructure and facilities. However, these challenges can be addressed through effective communication strategies and the development of new programs. The study concludes that optimal employee engagement is the key to the successful implementation of TQM in primary education environments.